A shoot derived long distance iron signal may act upstream of the IMA peptides in the regulation of Fe deficiency responses in Arabidopsis thaliana roots - García, María José; Angulo, Macarena; Romera, Francisco Javier; Lucena, Carlos; Pérez-Vicente, Rafael (Frontiers in Plant Science, 2022)
When plants suffer from Fe deficiency, they develop morphological and physiological responses, mainly in their roots, aimed to facilitate Fe mobilization and uptake. Once Fe has been acquired in sufficient quantity, the responses need to be switched off to avoid Fe toxicity and to conserve energy. Several hormones and signaling molecules, such as ethylene, auxin and nitric oxide, have been involved in the activation of Fe deficiency responses in Strategy I plants. These hormones and signaling molecules have almost no effect when applied to plants grown under Fe-sufficient conditions, which suggests the existence of a repressive signal related to the internal Fe content. The nature of this repressive signal is not known yet many experimental results suggest that is not related to the whole root Fe content but to some kind of Fe compound moving from leaves to roots through the phloem. After that, this signal has been named LOng-Distance Iron Signal (LODIS). Very recently, a novel family of small peptides, “IRON MAN” (IMA), has been identified as key components of the induction of Fe deficiency responses. However, the relationship between LODIS and IMA peptides is not known. The main objective of this work has been to clarify the relationship between both signals. For this, we have used Arabidopsis wild type (WT) Columbia and two of its mutants, opt3 and frd3, affected, either directly or indirectly, in the transport of Fe (LODIS) through the phloem. Both mutants present constitutive activation of Fe acquisition genes when grown in a Fe-sufficient medium despite the high accumulation of Fe in their roots. Arabidopsis WT Columbia plants and both mutants were treated with foliar application of Fe, and later on the expression of IMA and Fe acquisition genes was analyzed. The results obtained suggest that LODIS may act upstream of IMA peptides in the regulation of Fe deficiency responses in roots. The possible regulation of IMA peptides by ethylene has also been studied. Results obtained with ethylene precursors and inhibitors, and occurrence of ethylene-responsive cis-acting elements in the promoters of IMA genes, suggest that IMA peptides could also be regulated by ethylene.